2008
DOI: 10.1371/journal.ppat.1000166
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudomonas Quinolone Signal (PQS) Balances Life and Death in Pseudomonas aeruginosa Populations

Abstract: When environmental conditions deteriorate and become inhospitable, generic survival strategies for populations of bacteria may be to enter a dormant state that slows down metabolism, to develop a general tolerance to hostile parameters that characterize the habitat, and to impose a regime to eliminate damaged members. Here, we provide evidence that the pseudomonas quinolone signal (PQS) mediates induction of all of these phenotypes. For individual cells, PQS, an interbacterial signaling molecule of Pseudomonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
201
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 204 publications
(213 citation statements)
references
References 40 publications
11
201
0
1
Order By: Relevance
“…Although cells exposed to carbenicillin exhibit a dramatic morphology change, we found that exposure to tobramycin, but not carbenicillin, resulted in profile shifts of both PQS and AQNO families during swarming. This is in contrast to reports that have suggested a general PQS response to antimicrobials (22,26,27). Our findings are consistent with the hypothesis that AQ modulations following tobramycin exposure during pre-biofilm swarming should contribute to antibiotic tolerance (22,25,38), however, other factors must control P. aeruginosa tolerance to carbenicillin.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Although cells exposed to carbenicillin exhibit a dramatic morphology change, we found that exposure to tobramycin, but not carbenicillin, resulted in profile shifts of both PQS and AQNO families during swarming. This is in contrast to reports that have suggested a general PQS response to antimicrobials (22,26,27). Our findings are consistent with the hypothesis that AQ modulations following tobramycin exposure during pre-biofilm swarming should contribute to antibiotic tolerance (22,25,38), however, other factors must control P. aeruginosa tolerance to carbenicillin.…”
Section: Discussionsupporting
confidence: 89%
“…3A). This result agrees with prior reports that show PQS to be involved in cell death and swarm repression (22,24), and our CRM results that show the PQS subclass present at the swarm center under these conditions (Fig. S2).…”
Section: Pqs Promotes Cell Death and Reduced Swarming For Cells Expossupporting
confidence: 94%
See 3 more Smart Citations